An evaluation of the Parents Plus – Parenting When Separated programme. (April 2016) - Keating, Adele; Sharry, John; Murphy, Michelle; Rooney, Brendan; Carr, Alan
This study evaluated the Parents Plus – Parenting when Separated Programme, an intervention specifically designed to address the needs of separated parents in an Irish context. In a randomized control trial, 82 separated parents with young children were assigned to the Parents Plus – Parenting when Separated Programme treatment group and 79 to a waiting-list control group. They were assessed on measures of client goals, parenting satisfaction, child and parental adjustment and interparental conflict at baseline (Time 1) and 6 weeks later (Time 2), after the treatment group completed the Parents Plus – Parenting when Separated Programme. From Time 1 to 2, significant goal attainment, increases in parenting satisfaction and decreases in child behaviour problems, parental adjustment problems and interparental conflict occurred in the Parents Plus – Parenting when Separated Programme group, but not in the control group. These results supported the effectiveness of Parents Plus – Parenting when Separated Programme, which should be made more widely available to separated parents.